If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -1 = 5y + -4 Reorder the terms: -1 + 4y = 5y + -4 Reorder the terms: -1 + 4y = -4 + 5y Solving -1 + 4y = -4 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -1 + 4y + -5y = -4 + 5y + -5y Combine like terms: 4y + -5y = -1y -1 + -1y = -4 + 5y + -5y Combine like terms: 5y + -5y = 0 -1 + -1y = -4 + 0 -1 + -1y = -4 Add '1' to each side of the equation. -1 + 1 + -1y = -4 + 1 Combine like terms: -1 + 1 = 0 0 + -1y = -4 + 1 -1y = -4 + 1 Combine like terms: -4 + 1 = -3 -1y = -3 Divide each side by '-1'. y = 3 Simplifying y = 3
| -19/6+2r=-7/6 | | 50n=76 | | 9x^2+2=10x | | 9x^2+2=10x | | 4y+5x+3x-2x= | | 11(2x+8x)-10(10-11x)=912 | | -38=5(2x-1)+x | | 6x+3=x-12 | | 0=1785665535764547790876544213546r*5443 | | 5+2(3x+4)-x= | | (6-8i)(2+7i)= | | 102=-17a | | 1.67d+0.6=0.25(d-2) | | Mx+hx=p | | x=(6-8i)(2+7i) | | m/6+5=m/5+7 | | 17-.8(x-11)=.4(2x-11) | | ln(x)=-4 | | x-1/2+1=x+1 | | -1x=569278456756 | | x+x+1=x+3 | | 4/3(6y-27)=44 | | 9/10x=1/15-3/14 | | 4+3x-(2x-1)= | | 4x-7(2-x)=3x+2 | | -2=r+1 | | 7(3-n)= | | 0.35714257143=b/4.2 | | 45/(-9)= | | 17x^2-77x+24=0 | | 57/10+x=67/10 | | 40+.25x=25 |